1998
DOI: 10.1161/01.hyp.31.3.854
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Aortic Ring Contractions by Angiotensin II Antisense Peptide

Abstract: Abstract-Previous biochemical experiments have revealed two antisense peptide antagonists to human angiotensin II (Ang II), one encoded in the cDNA in the antiparallel reading, the other in the parallel reading. Neither peptide's ability to produce physiological antagonism has been demonstrated previously. Both peptides were tested for their ability to antagonize Ang II-induced contractions on rabbit aorta smooth muscle. Neither peptide had any direct contractile activity. The antiparallel Ang II peptide had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…2A). There are other examples of anti-peptides that have similar binding properties as the coded amino acid sequence in the literature (35,51). The analysis of hydropathic profiles of the coding and noncoding scFv73 CDR3 amino acid sequences revealed that they share a similar hydropathic pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). There are other examples of anti-peptides that have similar binding properties as the coded amino acid sequence in the literature (35,51). The analysis of hydropathic profiles of the coding and noncoding scFv73 CDR3 amino acid sequences revealed that they share a similar hydropathic pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among more than 40 examples (for review, see Ref. 34) hydropathic complementarity has been successfully applied to produce biologically active synthetic analogs of receptor binding sites (33,35,36) and ligands (37) and to map binding epitopes of natural ligands with their receptors (38,39). Also, hydropathic complementarity has been shown to determine several peptide-antibody interactions (40).…”
Section: Bacillus Thuringiensis (Bt)mentioning
confidence: 99%
“…In the present experimental system, however, the concentrations of TNF‐α in the culture supernatant were below the detection limit (1 pg mL −1 ) and the presence of anti‐TNF‐α antibody during infection did not reduce the LOX‐1 induction (data not shown). Furthermore, the addition of an angiotensin II receptor inhibitor peptide was also ineffective at 50 μM, which was far above the effective dose (Dillon et al , 1998) (Fig. 5).…”
Section: Resultsmentioning
confidence: 95%
“…In at least two cases --an antisense peptide to angiotensin II [27] and antisense peptides to enkephalins [28] --the antisense peptide enhanced peptide activity in vitro. The mechanism by which such enhancement occurs has not been elucidated, but might provide fertile ground for investigation.…”
Section: Peptide-peptide Interactionsmentioning
confidence: 99%